Medial Orbitofrontal Cortex Is Associated with Fatigue Sensation - Seiki Tajima; Shigeyuki Yamamoto; Masaaki Tanaka; Yosky Kataoka; Masao Iwase; Etsuji Yoshikawa; Hiroyuki Okada; Hirotaka Onoe; Hideo Tsukada; Hirohiko Kuratsune; Yasuomi Ouchi; Yasuyoshi Watanabe (Neurology Research International)
Fatigue is an indispensable bioalarm to avoid exhaustive state caused by overwork or stresses. It is necessary to elucidate the neural mechanism of fatigue sensation for managing fatigue properly. We performed H2O  15 positron emission tomography scans to indicate neural activations while subjects were performing 35-min fatigue-inducing task trials twice. During the positron emission tomography experiment, subjects performed advanced trail-making tests, touching the target circles in sequence located on the display of a touch-panel screen. In order to identify the brain regions associated with fatigue sensation, correlation analysis was performed using statistical parametric mapping method. The brain region exhibiting a positive correlation in activity with subjective sensation of fatigue, measured immediately after each positron emission tomography scan, was located in medial orbitofrontal cortex (Brodmann's area 10/11). Hence, the medial orbitofrontal cortex is a brain region associated with mental fatigue sensation. Our findings provide a new perspective on the neural basis of fatigue.